Алгоритм и методы хирургического лечения осложненных форм колоректального рака - Антипова, С.В.; Калинин, Е.В.; Шляхтин, В.В. (Iнститут експериментальної патології, онкології і радіобіології ім. Р. Є. Кавецького, 2009)
Проведено исследование результатов лечения 1022 больных, оперированных по поводу местнраспространенных и осложненных форм колоректального рака (586 больных раком прямой кишки и 436 больных раком ободочной кишки) за период с 1991 по 2008 г. Отмечено преобладание кишечной непроходимости (59,2%) из всех форм осложнений рака толстой кишки. В частности, заметное преобладание левосторонней локализации стенозирующего рака, в структуре обтурационной кишечной непроходимости у больных пожилого и старческого возраста. Сформулирована тактика оперативного лечения при осложненном раке толстой кишки различных локализаций опухоли. Ключевые слова: колоректальный рак, острая непроходимость толстой кишки, кровотечение, перфорация, перитонит, оперативное лечение. A study of treatment outcomes of 1022 patients operated on locally spread and complicated forms of colorectal cancer, including 586 patients with rectal cancer and 436 patients with colon cancer has been carried out. The analysis of patients with complicated forms of colon cancer has been performed in the department of general surgery for the period from 1991 to 2008. There was a predominance of intestinal impassability (59,2%) of all forms of complications of colon cancer. Besides, a predominance of left-sided location of stenosing canser has been noticed in the structure of obstructive intestinal impassability in elderly and senile patients. We formulated tactics of surgical treatment in complicated colon cancer with tumors of various locations. Key Words: colorectal cancer, acute impassability of colon, bleeding, perforation, peritonitis, surgical treatment.